Cataract-prone variants of γD-crystallin populate a conformation with a partially unfolded N-terminal domain under native conditions - Sara Volz; Jadyn R. Malone; Alex J. Guseman; Angela M. Gronenborn; Susan Marqusee (Proceedings of the National Academy of Sciences, 2025)
Human γD-crystallin, a monomeric protein abundant in the eye lens nucleus, must remain stably folded for an individual’s entire lifetime to avoid aggregation and protein deposition-associated cataract formation. γD-crystallin contains two homologous domains, an N-terminal domain (NTD) and a C-terminal domain (CTD), which interact via a hydrophobic interface. Several familial mutations in the gamma crystallin gene are linked to congenital early-onset cataract, most of which affect the NTD. Some of these, including V75D and W42R, are known to populate intermediates under partially denaturing conditions possessing a natively folded CTD and a completely unfolded NTD. We employed hydrogen–deuterium exchange mass spectrometry to probe the structural and energetic features of variants of γD-crystallin under both native and partially denaturing conditions. For V75D and W42R, we identify a species under native conditions that retains partial structure in the NTD and is structurally and energetically distinct from the intermediate populated under partially denaturing conditions. Residues at the NTD–CTD interface play crucial roles in stabilizing this intermediate, and disruption of interface contacts either by amino acid substitution or partial denaturation permits direct observation of two intermediates simultaneously. These data suggest that the intermediate identified under native conditions is accessed from the native state and not on the folding pathway. The intermediate we have identified here exposes hydrophobic amino acids that are buried in both the folded full-length protein and in the protein’s stable isolated domains. Such nonnative exposure of a hydrophobic patch may play an important role in cataract formation.